2021
DOI: 10.1136/bmjspcare-2021-002936
|View full text |Cite
|
Sign up to set email alerts
|

Global health-related quality of life in schizophrenia: systematic review and meta-analysis

Abstract: Background and aimSigns and symptoms of schizophrenia may have serious impacts on patients’ quality of life leading to concern about different aspects of their lives. This study presents a systematic review and meta-analysis of the studies examining the quality of life among patients with schizophrenia and its relationship with patients’ characteristics.Materials and methodsA total of 40 studies were extracted from searching of relevant databases published between 2000 and 2020. Descriptive data and correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Previous studies reported that individuals with severe mental disorders had difficulties participating in basic daily living tasks because of more preoccupation with the symptoms of illness, and severe psychiatric symptoms contribute to the decrease in QoL (De Pinho et al, 2018; Doroud et al, 2015; Hoseinipalangi et al, 2022). Therefore, disease symptoms are among the most important determinants that impair the QoL of people with schizophrenia, as stated in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that individuals with severe mental disorders had difficulties participating in basic daily living tasks because of more preoccupation with the symptoms of illness, and severe psychiatric symptoms contribute to the decrease in QoL (De Pinho et al, 2018; Doroud et al, 2015; Hoseinipalangi et al, 2022). Therefore, disease symptoms are among the most important determinants that impair the QoL of people with schizophrenia, as stated in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Research evidence suggests that the QoL of individuals with mental illness was lower than that of physically ill or healthy individuals (Berghöfer et al, 2020; Ginieri‐Coccossis et al, 2009). It has been reported in the literature that many factors such as social and economic difficulties, severe psychiatric symptoms, duration of mental illness, non‐adherence to treatment, frequent hospitalisations, lack of social support, unemployment and stigma contribute to the decrease in QoL in people with schizophrenia (De Pinho et al, 2018; Desalegn et al, 2020; Hoseinipalangi et al, 2022; Rocca et al, 2016). In addition, recent studies have shown the relationship between symptoms of the disease (negative and positive symptoms) and poor QoL as well as general psychopathology (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These studies suggest that schizophrenia can have a negative impact on the physical health and functioning of older patients, which in turn affects their quality of life. (Dong et al, 2019;Hoseinipalangi et al, 2022;Solomon et al, 2021). Therefore, focusing on patients' physiological functions, early detection of health problems, and physical health maintenance is imperative.…”
Section: Introductionmentioning
confidence: 99%